Single market emergency instrument: An instrument with pitfalls - Samina Sultan; Christian Rusche; Berthold Busch; Hubertus Bardt (Institut der deutschen Wirtschaft (IW), 2022)
In reaction to recent disruptions concerning the Single Market, the European Commission proposed an Emergency Instrument to maintain the proper functioning of the Single Market and ensure the supply and distribution of goods and services. It provides for far-reaching measures. The dirigiste interventions in the market it allows, are to be critically questioned, while better coordination and exchange of information between the member states could be an added value of the SMEI.
Keywords: 330